Optical Coherence Tomography Angiography Vessel Density Measurements in Eyes With Primary Open-Angle Glaucoma and Disc Hemorrhage. Issue 10 (October 2017) - Rao, Harsha L.; Pradhan, Zia S.; Weinreb, Robert N.; Dasari, Srilakshmi; Riyazuddin, Mohammed; Venugopal, Jayasree P.; Puttaiah, Narendra K.; Rao, Dhanaraj A.S.; Devi, Sathi; Mansouri, Kaweh; Webers, Carroll A.B.
Abstract : Purpose: To compare the vessel density measurements of optic nerve head, peripapillary and macular regions in severity-matched primary open-angle glaucoma (POAG) eyes with and without disc hemorrhage (DH) using optical coherence tomography (OCT) angiography, and to compare their diagnostic abilities with that of the rim area, retinal nerve fiber layer and the ganglion cell complex thickness measurements on OCT. Methods: In a cross-sectional study, 66 eyes of 46 control subjects, 34 eyes of 33 POAG patients with DH (median mean deviation=−3.7 dB) and 63 eyes of 43 POAG patients without DH (median mean deviation=−3.8 dB) underwent imaging with spectral domain OCT. Area under receiver operating characteristic curves (AUC) and 5sensitivities at 90% specificity of vessel density and structural measurements in POAG eyes with DH were compared with those in POAG eyes without DH. Results: Most of the vessel density and structural measurements were similar ( P >0.05) in POAG eyes with and without DH. Whole enface vessel density of the disc scan and inferotemporal peripapillary vessel density showed the best AUC and sensitivity at 90% specificity both in POAG eyes with DH (0.82, 56% and 0.75, 59%) and without DH (0.91, 73% and 0.83, 67%). AUCs and sensitivities of vessel density and structural measurements of POAG eyes with and without DH were statistically similar ( P >0.05). Conclusions: OCT angiography measured vessel densities and their diagnostic abilities in POAG eyes with and without DH were similar. This suggests that the cause of DH in POAG is unlikely to be vascular abnormality.